Exhausted CD8+ T cells exhibit low and strongly inhibited TCR signaling during chronic LCMV infection - Ioana Sandu (Nature Portfolio, 2020)
Excess antigenic exposure, such as in cancers or chronic viral infection, can lead to T cell exhaustion. Here the authors show that despite high exposure to antigen in the context of chronic LCMV infection in mice, exhausted CD8+ T cells have low levels of TCR signalling that can be reactivated by PD-L1 blockade.